МОДЕЛЮВАННЯ ТА КОРОТКОСТРОКОВЕ ПРОГНОЗУВАННЯ ТЕХНОЛОГІЧНОЇ СКЛАДОВОЇ ЕЛЕКТРИЧНОГО НАВАНТАЖЕННЯ ОБЛАСНОЇ ЕНЕРГОСИСТЕМИ - Черненко, П.А.; Мартинюк, О.В.; Мірошник, В.О. (Інститут електродинаміки НАН України, Київ, 2016)
The proposed method for a total electrical load of the regional electric power system forecasting is described. To model a technology load component, artificial intelligence techniques and autoregressive Box-Jenkins models are used. The advantages and disadvantages of different forecast models are analyze. To solve the mentioned task, an optimal type, architecture and vector of model input parameters are determined. Approbation was conducted on actual data taken from the regional electric power system with advantage of industrial power consumption. References 4, table 1.